Eschatological Expression In The Holy Text (A Preliminary Hermeneutical Exploration on Selected Eschatological Narratives in the Qur’an and the Bible) - Musadad, Asep Nahrul (Ar Raniry : International Journal of Islamic Studies, 2015)
One of the key concept that lies in almost every religions, as asserted in each holy texts, is eschatological doctrine. The apocalyptic belief in the last day has been existed throughout the history of civilizations with the various expression. Eschatological narrative in the holy texts ought to deemed as a historical text that revealed within its space and time. Accordingly, it is a historizing thing, which contains plenty of stories besides it’s sacred messages. This sense of historical awareness is pointed out – for example – by the eschatological narratives in the Qur’an which strongly influenced by socio-religious circumstances and topographical conditions in Arabian Peninsula at the time of revelation, as the Bible that has cased up its eschatological narratives based on a certain historical event: the destruction of Jerusalem in 70 AD by Roman soldiers. The central purpose of this paper is to explore the connection and influence of the certain historical moments on the style and construction of both, the Qur’an and the Bible eschatological narratives, through a simple hermeneutical analysis. Abstrak: Salah satu konsep kunci yang melandasi hampir seluruh agama, sebagaimana tertera dalam kitab-kitab sucinya adalah persoalan eskatologis. Kepercayaan apokaliptik akan adanya hari akhir terdapat hampir di setiap sejarah peradaban dalam beberapa ekspresi yang berbeda. Narasi eskatologis dalam beberapa teks suci hendaknya tidak hanya dilihat sebagai teks suci yang turun di ruang yang kosong. Dalam hal ini, ia menyejarah dan memberikan suatu kisah lain di samping pesan sakralnya. Hal ini terlihat jelas bagaimana narasi eskatologis dalam Al-Qur’an sangat dipengaruhi oleh kondisi sosio-religius dan keadaan topografis semenanjung Arab ketika itu. Begitu juga dengan Bibel yang mengemas narasi eskatologisnya berdasarkan suatu even sejarah tertentu, dalam hal ini penghancuran Yerusalem oleh bangsa Romawi pada tahun 70 M. Tulisan ini mencoba menakar keterpengaruhan narasi eskatologis dalam kedua kitab suci tersebut oleh beberapa entitas historis yang melingkupinya dengan menggunakan suatu analisis hermeneutis yang sederhana.Keywords: Eschatology, Phenomenology, Hermeneutic, Al-Qur’an, Bible